2020
DOI: 10.1001/jamanetworkopen.2019.19433
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anatomic Restoration of Distal Radius Fractures Among Older Adults

Abstract: IMPORTANCE The value of precise anatomic restoration for distal radius fractures (DRFs) in older adults has been debated for many decades, with conflicting results in the literature. In light of the growing population of adults aged 60 years and older, both fracture incidence and associated treatment costs are expected to increase. OBJECTIVE To determine the association between radiographic measures of reduction and patient outcomes after DRF in older patients. DESIGN, SETTING, AND PARTICIPANTS Data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
4
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 50 publications
(125 reference statements)
4
27
4
11
Order By: Relevance
“…39 – 43 However, multiple studies have also suggested that clinically important differences in the outcomes are not associated with anatomic radiographic reduction parameters and that other factors may play a more important role. 27 , 44 52 This study supports that near-anatomic reduction, especially at the time of long-term follow up, may provide no clinically important additional benefit. More studies are needed to evaluate whether a poor anatomic reduction leads to long-term issues due to potential changes in carpal stability and radiocarpal degenerative changes.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…39 – 43 However, multiple studies have also suggested that clinically important differences in the outcomes are not associated with anatomic radiographic reduction parameters and that other factors may play a more important role. 27 , 44 52 This study supports that near-anatomic reduction, especially at the time of long-term follow up, may provide no clinically important additional benefit. More studies are needed to evaluate whether a poor anatomic reduction leads to long-term issues due to potential changes in carpal stability and radiocarpal degenerative changes.…”
Section: Discussionsupporting
confidence: 54%
“… 2 , 3 Much of the research regarding the outcomes of distal radius fracture ORIF has focused on postoperative complications and the restoration of anatomic alignment. 1 , 4 6 …”
mentioning
confidence: 99%
“…reported and objective functional outcome measures among 166 patients aged 60 years or older who completed 12-month assessments. 1 In keeping with other similar analyses of both older 2,3 and younger 4 patients, Chung et al 1 found little association of patients' radiographic measurements with their outcomes. This is important because the rationale for intervening surgically is essentially based on the premise that restoring the patient's preinjury anatomy will provide better outcomes when the fracture heals.…”
mentioning
confidence: 56%
“…Distal radius fractures (DRF) are one of the most common types of fractures in orthopedics [1,2] .With an ageing population, the incidence of distal radius fracture is increasing [3,4] .Currently, there are two main methods for treating distal radius fractures, surgical and nonsurgical [1,[5][6][7] . However, whichever the method is adopted, there will still be different degrees of wrist joint dysfunction, such as pain, swelling, joint range of motion and strength decline after fracture, affecting the daily life and work [8,9] .It is of great signi cance to explore a simple, effective and scienti c functional rehabilitation exercise.…”
Section: Introductionmentioning
confidence: 99%